THE DEVELOPMENT OF WARAK DANCE PRESENTATION FORMS IN SEMARANG CITY - Kaeksi, Maharani Hares (Institut Seni Indoensia Surakarta, 2025)
The Warak Dhugdhèr dance is a form of creation dance in Semarang city. In its performance, the dance brings the property of warak ngêndhog, a mythological creatures in the dhugdhèran tradition symbolizing the unity of Javanese, Chinese, and Arabic cultures. This dance was created by Didik Nini Thowok and Yoyok Bambang Priyambodo and first performed was in 2006. In its development, innovations emerged in new Warak dance forms that were performed at the Warak Dance Festival and also in the community environment. This study aims to analyze the development of Warak dance presentation forms that have grown and developed in Semarang. This study uses a qualitative research method with an ethnochoreology approach in its application. The methods applied in this study consist of the stages of problem identification, data collection, data analysis, and conclusions. The findings reveal that adaptation and innovation are manifested in structural changes, such as choreography, music, makeup and costume, and the form of warak itself. Three main directions of development: the preservation of Warak ngêndhog iconography as properties, adaptation to the socio-cultural context, and the emergence of several new forms of Warak Dance such as the Manggar Warak dance, Ronggeng Warak dance, and Semarak Warak dance. These developments are driven by the creative reinterpretation of the artists who created it, government policies regarding culture, and community participation. This study concludes that new forms of Warak Dance have grown dynamically through processes of adaptation and innovation. Innovation and development efforts are also continuously carried out in order to adapt to the socio-cultural conditions in Semarang city.